Online Gaming and Healthy Lifestyles: A Qualitative Study of Gamers in Saudi Arabia - Yara Almuhtadi; Samah Alageel (Societies)
Gamers and esports players encounter distinct health challenges that can affect their well-being and performance. Recognising these needs is crucial for developing effective health interventions. This study explored the barriers and facilitators to adopting a healthy lifestyle among gamers and their views on behaviour change interventions. We conducted semi-structured interviews with esports competitors and gamers, using the COM-B model to explore their perceptions. Participants discussed definitions of a healthy lifestyle, emphasising diet and physical activity. There was no consensus on its attainability, as personal, social, and environmental factors influenced perceptions of ease or difficulty. Participants identified key aspects for effective behaviour change interventions, including where, how, and when to implement them, considering these components can help in the design of interventions that are more effective, accessible, and engaging for the target population. This study highlights the importance of a comprehensive approach that considers the unique traits of gamers and their lifestyle. By tailoring health promotion efforts, policymakers can more effectively support this community in reaching its health and wellness objectives.